Mast cells, glia and neuroinflammation: partners in crime?. Issue 3 (March 2014) - Skaper, Stephen D.; Facci, Laura; Giusti, Pietro
Summary Glia and microglia in particular elaborate pro‐inflammatory molecules that play key roles in central nervous system (CNS) disorders from neuropathic pain and epilepsy to neurodegenerative diseases. Microglia respond also to pro‐inflammatory signals released from other non‐neuronal cells, mainly those of immune origin such as mast cells. The latter are found in most tissues, are CNS resident, and traverse the blood–spinal cord and blood–brain barriers when barrier compromise results from CNS pathology. Growing evidence of mast cell–glia communication opens new perspectives for the development of therapies targeting neuroinflammation by differentially modulating activation of non‐neuronal cells that normally control neuronal sensitization – both peripherally and centrally. Mast cells and glia possess endogenous homeostatic mechanisms/molecules that can be up‐regulated as a result of tissue damage or stimulation of inflammatory responses. Such molecules include the N‐acylethanolamine family. One such member, N‐palmitoylethanolamine is proposed to have a key role in maintenance of cellular homeostasis in the face of external stressors provoking, for example, inflammation. N‐Palmitoylethanolamine has proven efficacious in mast‐cell‐mediated experimental models of acute and neurogenic inflammation. This review will provide an overview of recent progress relating to the pathobiology of neuroinflammation, the role of microglia, neuroimmune interactions involving mast cells and the possibility that mast cell–microglia cross‐talk contributes to the exacerbation of acute symptoms of chronic neurodegenerative disease and accelerates disease progression, as well as promoting pain transmission pathways. We will conclude by considering the therapeutic potential of treating systemic inflammation or blockade of signalling pathways from the periphery to the brain in such settings.